Assessing changing relations between the Russian Federation and South Africa - Daniel, Omaduore Rosaline (Department of Political Studies, 2016)
This study aims to assess how Russia's relations with South Africa have changed since the end of the Cold War. The study draws on social constructivism as a theoretical framework to show that the ideals and beliefs of the Russian Federation as a great power have not disappeared with the collapse of the Soviet Union. The West seeks to set the terms of Russia's engagement in international relations, but Russia is certain about its belief in taking its rightful place in global affairs. The study argues that Africa provides a source of economic expansion for Russia. Moreover, South Africa, as a significant economic and political actor in the continent that subscribes to similar ideals, can help Russia to reassert its status as a major world power. The study traces voting patterns of Russia and South Africa within the UN Security Council, and discusses opportunities in the BRICS forum (spanning four continents) for bilateral economic engagement. Collaboration with South Africa in the Security Council and in BRICS, it is argued, helps Russia to assume a more global role, and also ascribes a level of international prestige to both Moscow and Pretoria. The dissertation concludes that economic and geopolitical necessity is the main reason for changing relations between Russia and South Africa since the Soviet era.